Genetic loci associated with freezing tolerance in a European rapeseed (Brassica napus L.) diversity panel identified by genome‐wide association mapping. (25th May 2022) - Chao, Wun S.; Li, Xuehui; Horvath, David P.; Anderson, James V.
Abstract: Winter biotypes of rapeseed ( Brassica napus L.) require a vernalization treatment to enter the reproductive phase and generally produce greater yields than spring rapeseed. To find genetic loci associated with freezing tolerance in rapeseed, we first performed genotyping‐by‐sequencing (GBS) on a diversity panel consisting of 222 rapeseed accessions originating primarily from Europe, which identified 69, 554 high‐quality single‐nucleotide polymorphisms (SNPs). Model‐based cluster analysis suggested that there were eight subgroups. The diversity panel was then phenotyped for freezing survival (visual damage and Fv/Fo and Fv/Fm) after 2 months of cold acclimation (5°C) and a freezing treatment (−15°C for 4 h). The genotypic and phenotypic data for each accession in the rapeseed diversity panel was then used to conduct a genome‐wide association study (GWAS). GWAS results showed that 14 significant markers were mapped to seven chromosomes for the phenotypes scored. Twenty‐four candidate genes located within the mapped loci were identified as previously associated with lipid, photosynthesis, flowering, ubiquitination, and cytochrome P450 in rapeseed or other plant species.